2015
DOI: 10.1093/glycob/cwv092
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a family 43 β-xylosidase from the xylooligosaccharide utilizing putative probioticWeissellasp. strain 92

Abstract: In this work, we present the first XOS degrading glycoside hydrolase from Weissella, WXyn43, a two-domain enzyme from GH43. The gene was amplified from genomic DNA of the XOS utilizing Weissella strain 92, classified under the species-pair Weissella cibaria/W.confusa, and expressed in Escherichia coli. The enzyme is lacking a putative signal peptide and is, from a homology model, shown to be composed of an N-terminal 5-fold β-propeller catalytic domain and a C-terminal β-sandwich domain of unknown function. WX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Values with different superscripts in the same column are significantly different (P < 0.05). The main hydrolysis product xylose, X1, a product of the reaction catalysed by X2 and X3, is the same as previously reported (Falck et al 2016;L opez-Hern andez et al 2018). W. confuse L9 exert the b-xylosidase which degraded xylobiose and xylotriose to xylose as a final product (L opez-Hern andez et al 2018).…”
Section: Cellulosesupporting
confidence: 81%
See 3 more Smart Citations
“…Values with different superscripts in the same column are significantly different (P < 0.05). The main hydrolysis product xylose, X1, a product of the reaction catalysed by X2 and X3, is the same as previously reported (Falck et al 2016;L opez-Hern andez et al 2018). W. confuse L9 exert the b-xylosidase which degraded xylobiose and xylotriose to xylose as a final product (L opez-Hern andez et al 2018).…”
Section: Cellulosesupporting
confidence: 81%
“…The main hydrolysis product xylose, X1, a product of the reaction catalysed by X2 and X3, is the same as previously reported (Falck et al . ; López‐Hernández et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…XOS are not digestible by human enzymes, but stimulate selectively the growth of beneficial gastrointestinal flora, such as lactic acid bacteria and bifidobacteria. In vitro assays have shown that X 2 and X 3 promote the growth of Bifidobacterium adolescentis , B. infantis , B. longum , B. bifidum (reviewed by Vázquez et al [ 123 ]) and lactic acid bacteria such as Lactobacillus brevis [ 37 ] including new potential probiotic strains of Weissella [ 124 , 125 ] while short AXOS are more selective for Bifidobacterium strains [ 14 , 31 ]. Other biological effects tested in vitro are antimicrobial effects of acidic xylooligosaccharides, such as aldotetrauronic and aldopentauronic acids [ 58 ], and antioxidant activities of XOS from sugarcane bagasse [ 70 ].…”
Section: Further Development Of Enzymatic Processing For Production Omentioning
confidence: 99%